ผลของการใช้รูปแบบพยาบาลพี่เลี้ยงต่อความสามารถในการปฏิบัติงานของพยาบาลที่สำเร็จการศึกษาใหม่ - ศิริมา โกมารทัต (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this quasi-experimental research was to study effect of nursing competency of new graduated nurses after using the mentorship model. Research subjects consisted of 19 new graduated nurses who worked with a trained mentor for 1 month. Research instruments were mentorship model for new graduated nurses program, a manual of mentorship model for new graduated nurses, Mentorship Knowledge Questionnaire (MKQ), Activities of Mentorship Model Evaluation Questionnaire (AMMAQ), and Nursing Competency Evaluation of New graduated nurses Questionnaire (NCEQ). Panel experts tested all instruments for content validity. The reliability of MKQ, AMMAQ, NCEQ were 1,.90 and .96 respectively. According to the experiment, new graduated nurses were evaluated Nursing Competency by head nurses before experiment twice. (1 month- interval between Time 1 and Time 2). After that mentors were trained the roles of advisor and counselor, teacher, sponsor and resource facilitator. When the mentors passed the evaluation of being a mentorship. The mentor and new graduated nurse worked together for 1 month. After the experiment, new graduated nurses were evaluated Nursing Competency by head nurses again (Time 3). All data were analyzed by median, quartile deviation and Wilcoxon Signed Ranks test. Major finding was as follows: Nursing competency of new graduated nurses after the experiment were significantly higher than before the experiment at the .05 level